The case for alternative endpoints in computing education. (27th April 2021) - Tissenbaum, Mike; Weintrop, David; Holbert, Nathan; Clegg, Tamara
Abstract: This paper argues for a re‐examination of the nature and goals of broad computing education initiatives. Instead of starting with specific values or goals, we instead begin by considering various desired endpoints of computing instruction and then work backward to reason about what form learning activities might take and what are the underlying values and principles that support learners in reaching these endpoints. The result of this exercise is a push for rethinking the form of contemporary computing education with an eye toward more diverse, equitable and meaningful endpoints. With a focus on the role that constructionist‐focused pedagogies and designs can play in supporting these endpoints, we examine four distinct cases and the endpoints they support. This paper is not intended to encompass all the possible alternate endpoints for computer science education; rather, this work seeks to start a conversation around the nature of and need for alternate endpoints, as a means to re‐evaluate the current tools and curricula to prepare learners for a future of active and empowered computing‐literate citizens. Practitioner notes What is already known about this topic There is a growing call for computing education to be a core educational component. Computing education traditionally has a narrow goal of training people for programming jobs. Computing education fails to connect with students underrepresented in STEM. What this paper adds An argument for why we need more and diverse endpoints to computing education. That many possible endpoints for computing education can be more inclusive, just and equitable than software engineering. Constructionism is a particularly useful paradigm for approaching and supporting alternate endpoints. Implications for practice and policy Helps reframe the goals of computing education, to truly be "for all." Provides a set of cases for how this reframing can be achieved. Gives policy new lenses for understanding, evaluating and implementing computing education.